Parakinesia: a Delphi consensus report - Foucher, Jack R.; Bartsch, Andreas J.; Mainberger, Olivier; Vercueil, Laurent; de Billy, Clément C.; Obrecht, Alexandre; Arcay, Hippolyte; Berna, Fabrice; Clauss, Julie M. E.; Weibel, Sébastien; Hanke, Markus; Elowe, Julien; et al. (Schizophrenia research, 2024)
Abnormal movements are intrinsic to some forms of endogenous psychoses. Spontaneous dyskinesias are observed in drug-naïve first-episode patients and at-risk subjects. However, recent descriptions of spontaneous dyskinesias may actually represent the rediscovery of a more complex phenomenon, ‘parakinesia’ which was described and documented in extensive cinematographic recordings and long-term observations by German and French neuropsychiatrists decades before the introduction of antipsychotics. With the emergence of drug induced movement disorders, the description of parakinesia has been refined to emphasize the features enabling differential diagnosis with tardive dyskinesia. Unfortunately, parakinesia was largely neglected by mainstream psychiatry to the point of being almost absent from the English-language literature. With the renewed interest in motor phenomena intrinsic to SSD, it was timely not only to raise awareness of parakinesia, but also to propose a scientifically usable definition for this phenomenon. Therefore, we conducted a Delphi consensus exercise with clinicians familiar with the concept of parakinesia. The original concept was separated into hyperkinetic parakinesia (HPk) as dyskinetic-like expressive movements and parakinetic psychomotricity (PPM), i.e., patient's departing from the patient's normal motion style. HPk prevails on the upper part of the face and body, resembling expressive and reactive gestures that not only occur inappropriately but also appear distorted. Abnormal movements vary in intensity depending on the level of psychomotor arousal and are thus abated by antipsychotics. HPk frequently co-occurs with PPM, in which gestures and mimics lose their naturalness and become awkward, disharmonious, stiff, mannered, and bizarre. Patients are never spontaneously aware of HPk or PPM, and the movements are never experienced as self-dystonic or self-alien. HPk and PPM are highly specific to endogenous psychoses, in which they are acquired and progressive, giving them prognostic value. Their differential diagnoses and correspondences with current international concepts are discussed.